ANALYSIS OF SOCIO-CULTURAL CHANGE: THE CHALLENGES OF MULTICULTURAL AND RADICALISM IN ISLAMIC EDUCATION - Agus Sukamto; Nanik Nurvayanti; Zamroni Zamroni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Rapid social and cultural changes, particularly as a result of advances in information and communication technology, present various challenges for Islamic education. Islamic education must be able to adapt to multicultural dynamics without sacrificing the fundamental values of religious teachings. This study examines the challenges arising from the implementation of multicultural education in an Islamic context and the threat of radicalism that can disrupt social harmony. The research was conducted through a literature review that synthesized various current literature on multiculturalism, radicalism, and Islamic education. The results indicate that Islamic education plays a strategic role in instilling values of tolerance, moderation, and respect for cultural, religious, and ethnic diversity in pluralistic Indonesia. Furthermore, Islamic education serves as a primary bulwark in preventing radicalism through curriculum strengthening, teacher training, and family and community involvement. An inclusive and adaptive approach to the curriculum, along with cross-cultural and interfaith dialogue, are key to building a harmonious, peaceful, and just society. Deradicalization efforts through Islamic education need to be systematically and sustainably designed to foster a moderate and open generation.